An Ultra‐Strong, Water Stable and Antimicrobial Chitosan Film with Interdigitated Bouligand Structure. (31st May 2022) - Li, Suiyi; Wang, Haohao; Huang, Dafang; Liu, Jia; Chen, Chuchu; Li, Dagang; Zhu, Mingwei; Chen, Yanfeng
Abstract: Natural polymeric materials are an attractive potential replacement for non‐biodegradable plastics. However, one of the main challenges for high‐end applications of these materials, is to maintain their high mechanical properties in a watery environment. Here, inspired by the reinforcement principle of multiscale architecture in natural crab exoskeletons, an ultra‐strong and hydrostable film is developed through a top‐down method directly from the crab shell. The resulting chitosan film exhibits an outstanding isotropic tensile strength of ≈ 220 MPa and a superior wet strength of ≈ 70 MPa, which is significantly higher than that of conventional polysaccharide‐based materials and many commercially used plastics. Its excellent mechanical properties are due to the realization of strong interactions between chitosan fibrils even in wet conditions through interdigitation and densification processes without other additives. Additionally, it also possesses outstanding transparency, flexibility, antimicrobial ability, and biodegradability, making it a promising high‐performance and eco‐friendly material for many potential applications. Abstract : Inspired by the reinforcement principle of multiscale architecture in crab exoskeletons, strong, hydrostable, and antimicrobial chitosan films with Bouligand structure directly from crab shell, prepared by a facile top‐down method are fabricated. The resulting film exhibits outstanding mechanical properties in dry and wet states, which are significantly improved compared to those of conventional polysaccharide‐based materials and many commercially used plastics.